Dynamic behaviour of timber footbridges - Negrão, João (2004)
In ENV1995-2:1997 (Eurocode 5-Part 2), a simplified method is proposed for checking the serviceability limit state (SLS) of vibration in timber bridges subjected to the action of streams of pedestrians. The procedure estimates the values of peak acceleration in the deck under such conditions. This paper undertakes a comparison between the values supplied by that method and those obtained through a Finite-Element based numerical analysis. A number of load cases is analysed, in which variable values of the number of pedestrians and of its walking frequency is considered. The probabilistic models used to generate the dynamic loading corresponding to these crowds are also described.